Study of the neuroprotective properties of metformin in rats with type 2 diabetes mellitus and brain injury induced by intracerebral hemorrhage - V.L. Holubiev; M.H. Oberemok; V.A. Tkachenko; Yu.V. Kharchenko; O.O. Bondarenko; A.E. Lievykh; V.I. Zhyliuk (Medičnì Perspektivi)
The aim of this study was to study the effect of metformin (Met) on the formation of the conditional passive avoidance skills, markers of neurogenesis and oxidative stress in the brain of rats with acute intracerebral hemorrhage (ICH) in the setting of streptozotocin-nicotinamide-induced diabetes. Type 2 diabetes mellitus (T2DM) was induced in rats via the intraperitoneal injection of streptozotocin (STZ) and nicotinamide (NA), ICH – by microinjection of bacterial collagenase into the striatum. Rats were randomly divided into four groups: 1 – intact animals (n=8), 2 – T2DM (n=9); 3 – T2DM+ICH (n=7); 4 – T2DM+ICH+Met (n=7). The passive avoidance test was used to evaluate behavioural activity. Advanced oxidation protein products (AOPP) and lactate were measured by spectrophotometry, advanced glycation end products (AGEs) by quantitative fluorescence, level of 8-hydroxy-2-deoxyguanosine (8-OHdG) was assessed by enzyme-linked immunosorbent assay (ELISA). Histopathological examination was performed using general histological staining techniques and immunohistochemical methods for assessment of expression of endothelial NO-synthase (eNOS), Growth Associated Protein 43 (GAP43), Hypoxia-inducible factor 1-alpha (HIF-1α), neural cadherine (N-cadherine) and vascular endothelial cadherine (VE-cadherine). In this study, metformin had nootropic (anti-amnestic) activity and decreased oxidative stress markers (AGEs, AOPPs and 8-OHdG) levels by 29.1% (p<0.001), 24.9% (p<0.015) and 29.3% (p<0.05) respectively, which indicates its positive impact on the course of free radical oxidation reactions intensified by both diabetes and intracerebral hemorrhage. The study provides additional information on neuroprotective properties of metformin and the emphasizes possibility of using metformin in diabetic patients at risk of hemorrhagic stroke. Considering the increase in VE-cadherin expression by the drug, it is possible to predict its positive effect on the function of blood-brain barrier. This study may serve as a reference for the feasibility of studying the clinical efficacy of metformin under these conditions.